Knowledge of primary healthcare workers regarding the prevention and control of non-communicable diseases in Osun State, Nigeria: A rural-urban comparison - Adebowale F. Akinwumi; Olapeju A. Esimai; Olusola Fajobi; Ajibola Idowu; Oluwaseun T. Esan; Temitope O. Ojo (AOSIS, 2021)
Background: There is a rising burden of non-communicable diseases (NCDs) in the sub-Saharan Africa, and calls for integration of management of selected NCDs with primary healthcare (PHC) have been unrelenting. Cost-effective interventions for the prevention and control of NCDs can be delivered at PHC facilities in low-resource settings by clinical healthcare workers (HCWs). Aim: This study compared the knowledge of HCWs in PHC facilities regarding the prevention and control of NCDs in rural and urban local government areas (LGAs) of Osun State. Setting: A comparative cross-sectional study was conducted amongst 400 eligible HCWs recruited using a multistage sampling technique in PHC facilities of six rural and six urban LGAs. Methods: A pretested self-administered case-scenarios questionnaire was used to assess the knowledge of HCWs regarding the prevention and control of three selected NCDs (diabetes, hypertension and chronic respiratory diseases). Both descriptive and inferential statistics were conducted. Results: The mean knowledge scores of HCWs regarding the prevention and control of the three NCDs were 17.76 ± 4.41 in rural and 17.62 ± 4.02 in urban LGAs out of 30 maximum scores. The proportion of HCWs with adequate knowledge in the rural LGAs (31.0%) was slightly higher than the urban LGAs (23.0%); however, it was not statistically significant (χ2 = 3.247; p = 0.072). The major determinants of adequate knowledge include cadre of HCWs, location, years in practice with professional certificate, NCD training course attendance and reported experience managing diabetic patients. Conclusion: The HCWs in PHC facilities in rural and urban LGAs of Osun State, Nigeria, had a poor knowledge regarding the prevention and control of NCDs. Training and re-training of less-skilled HCWs in the PHC facilities using relevant WHO NCD protocols and guidelines are imperatives to improve their knowledge about the prevention and control of NCDs.